2021
DOI: 10.1213/ane.0000000000005431
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Ionized Calcium Concentrations During Hemostatic Transfusion and Calcium Treatment With Mortality in Major Trauma

Abstract: BACKGROUND: Transfusion of citrated blood products may worsen resuscitation-induced hypocalcemia and trauma outcomes, suggesting the need for protocolized early calcium replacement in major trauma. However, the dynamics of ionized calcium during hemostatic resuscitation of severe injury are not well studied. We determined the frequency of hypocalcemia and quantified the association between the first measured ionized calcium concentration [iCa] and calcium administration early during hemostatic resuscitation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
(49 reference statements)
0
27
1
Order By: Relevance
“…Mortality was higher in the iCa <0.90 mmol/L group -49% death rate versus 24% in the iCa ≥0.90 group (p = .007). In addition, patients in the iCa <0.90 mmol/L group received more blood products (34 [23-58] vs. 22 [18][19][20][21][22][23][24][25][26][27][28][29][30] units, p < .001) and calcium chloride (4 [2][3][4][5][6][7] vs. 3 [1][2][3][4] g, p = .002), possibly showing a bias by indication in this study. There was no difference in the duration (hours) of the MTP or final iCa levels.…”
Section: Resultsmentioning
confidence: 99%
“…Mortality was higher in the iCa <0.90 mmol/L group -49% death rate versus 24% in the iCa ≥0.90 group (p = .007). In addition, patients in the iCa <0.90 mmol/L group received more blood products (34 [23-58] vs. 22 [18][19][20][21][22][23][24][25][26][27][28][29][30] units, p < .001) and calcium chloride (4 [2][3][4][5][6][7] vs. 3 [1][2][3][4] g, p = .002), possibly showing a bias by indication in this study. There was no difference in the duration (hours) of the MTP or final iCa levels.…”
Section: Resultsmentioning
confidence: 99%
“…Giancarelli et al only looked at ionized calcium at one moment in time whereas we looked over a period to review a trajectory and assess for potential timing of intervention. Several recent studies have measured the incidence of hypocalcemia during massive transfusion and found similarly high incidences [7,[9][10][11].…”
Section: Previous Studies On Hypocalcemia From Massive Transfusionmentioning
confidence: 95%
“…Clinical signs of hypocalcemia include heart failure, prolonged QT interval, sinus tachycardia, paresthesia, muscle spasms, cramps, tetany, circumoral numbness, and seizures [8]. Given the integral role that calcium plays in coagulation and hemodynamics, it is no surprise that several studies have shown a correlation between hypocalcemia and mortality [7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…There are no prospective data demonstrating that calcium replacement improves survival. Indeed, Chanthima et al [43 ▪ ] found no relationship between mortality and first ionized calcium level, or calcium supplementation corrected for citrate load.…”
Section: Calciummentioning
confidence: 99%